2009
DOI: 10.1186/1475-2859-8-4
|View full text |Cite
|
Sign up to set email alerts
|

Learning about protein solubility from bacterial inclusion bodies

Abstract: The progressive solving of the conformation of aggregated proteins and the conceptual understanding of the biology of inclusion bodies in recombinant bacteria is providing exciting insights on protein folding and quality. Interestingly, newest data also show an unexpected functional and structural complexity of soluble recombinant protein species and picture the whole bacterial cell factory scenario as more intricate than formerly believed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
43
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 59 publications
2
43
0
1
Order By: Relevance
“…On the other hand, the overall mGFP specific fluorescence in the presence of DnaK/DnaJ was lower than in the absence of these chaperones. This is consistent with recent observations reporting that higher protein yield in a production process necessarily results in a decrease of conformational quality (10,16,18). To determine whether the positive effect of DnaK and DnaJ in assisting protein folding could be extended to the expression of other recombinant proteins in insect cells, we also tested coexpression of these proteins with foot-and-mouth disease virus (FMDV) VP1 and VP2 capsid proteins and human alphagalactosidase A.…”
supporting
confidence: 58%
“…On the other hand, the overall mGFP specific fluorescence in the presence of DnaK/DnaJ was lower than in the absence of these chaperones. This is consistent with recent observations reporting that higher protein yield in a production process necessarily results in a decrease of conformational quality (10,16,18). To determine whether the positive effect of DnaK and DnaJ in assisting protein folding could be extended to the expression of other recombinant proteins in insect cells, we also tested coexpression of these proteins with foot-and-mouth disease virus (FMDV) VP1 and VP2 capsid proteins and human alphagalactosidase A.…”
supporting
confidence: 58%
“…4 bacteria, the most common protein production platform, often yields recombinant polypeptides totally or partially deposited as inclusion bodies. 5 although recent studies have shown that inclusion bodies might contain functional protein species suitable for in situ enzymatic reactions, [6][7][8][9][10][11][12] protein production processes are in general aimed at soluble species. therefore, inclusion bodies are separated by differential sedimentation and further discarded.…”
mentioning
confidence: 99%
“…BL21-DE3-pLysS was the selected strain for large scale expression because of its capacity to suppress the basal expression of the T7 promoter due to the production of T7 lysozyme, a natural inhibitor of T7 RNA polymerase. The extraction of the expressed protein from E. coli BL21-DE3-pLysS cells demonstrated that the MP was present only in the insoluble fraction, probably as the result of inclusion bodies formation (Martínez-Alonso et al, 2009). Similar cases of insolubility of proteins expressed in E. coli system were reported with the replicases of Tobacco mosaic virus (TMV) and Citrus tristeza virus (CTV) (Hills et al, 1987;Çevik et al, 2008) and with TMV MP (Chen et al, 2000).…”
mentioning
confidence: 53%